Reclaiming the Spirit of Jordan’s Principle: Lessons from a Canadian Human Rights Tribunal Ruling - Churchill, Molly; Sinha, Vandna (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2018)
Jordan’s Principle is a child-first principle designed to ensure First Nation children do not experience delays, denials, or disruptions of services ordinarily available to other children in Canada. It was envisioned as a human rights principle tailored to address the unique risks of inequitable treatment arising from the complex structure of public services for First Nations. In 2016, the Canadian Human Rights Tribunal (CHRT) found the federal government’s failure to implement Jordan’s Principle constitutes discrimination on the basis of race and/or national or ethnic origin, and ordered the federal government to cease this discrimination. In response, the First Nations Child and Family Caring Society, one of the complainants in the case and a primary champion of Jordan’s Principle, called on the federal government to implement the principle immediately in keeping with the conclusions laid out in a 2015 report by the Jordan’s Principle Working Group (JPWG, 2015). This article provides an overview of the research presented and conclusions drawn in the report, integrating analysis of the initial CHRT rulings on Jordan’s Principle and of access to information documents received in the year following release of the report. Focusing on the rulings that the CHRT issued between January and September of 2016, we highlight requirements that the CHRT ruled the federal government must fulfill, as well as additional considerations that should be taken into account in implementing Jordan’s Principle. Résumé Le principe de Jordan est un principe de l’enfant d’abord qui vise à assurer que tous les enfants des Premières Nations reçoivent, sans délai, refus ou perturbation, les services qui seraient habituellement à la disposition des autres enfants au Canada. Il s’agissait d’un principe des droits de la personne conçu pour remédier aux risques uniques d’un traitement inéquitable découlant de la structure complexe des services publics pour les Premières Nations. Le Tribunal canadien des droits de la personne (TCDP) a récemment conclu que la non-application du principe de Jordan par le gouvernement fédéral constituait une discrimination fondée sur la race et/ou l’origine nationale ou ethnique et a ordonné au gouvernement fédéral de mettre fin à cette discrimination. En réponse, la Société de soutien à l’enfance et à la famille des Premières Nations du Canada, l’un des plaignants dans l’affaire et l’un des principaux défenseurs du principe de Jordan, a fait appel au gouvernement fédéral afin de mettre en œuvre ce principe immédiatement, conformément aux conclusions du rapport de 2015 du groupe de travail sur le principe de Jordan. Cet article donne un aperçu des recherches présentées et des conclusions du rapport, en intégrant l’analyse des décisions du TCDP sur le principe de Jordan et les documents d’accès récemment reçus. En nous concentrant sur les décisions rendues par le TCDP entre janvier et septembre 2016, nous soulignons les exigences que le TCDP a imposées au gouvernement fédéral, ainsi que des considérations supplémentaires à prendre en compte lors de la mise en œuvre du principe de Jordan. Mots clés: Premières Nations; autochtones; droits de l’enfant; principe de Jordan; égalité réelle; fonction publique; Tribunal canadien des droits de la personne; TCDP